Some aspects of nursery rearing of the Asian seabass (Lates calcarifer, Bloch) in indoor cement tanks - Philipose, K. K.; Krupesha Sharma, S. R.; Sadhu, N.; Vaidya, N. G.; Rao, G. Syda (Indian Journal of Fisheries, 2011)
Asian seabass (Lates calcarifer) is a highly valued food fish of great culture potential. Nursery rearing of Asian seabass in indoor cement tanks was undertaken. Fish were fed on artificial diets at 4% body weight and four times feeding per day with periodical size grading. Mean weight and length at the end of the 45 days experimental period was 8.55 g and 91.03 mm, respectively. While survival rate was 100%, FCR and PER at the end of the 45 days experimental period was 1.15 and 1.07%, respectively. The results of various growth parameters studied showed that the values obtained were in conformity with earlier reports on nursery rearing of Asian seabass under varied rearing systems and growth conditions.